Surface air temperature - J.E. Overland; Edward Hanna; I. Hanssen-Bauer; S.-J. Kim; J.E. Walsh; M. Wang; U.S. Bhatt; R.L. Thoman (2018)
•The average annual surface air temperature anomaly over land north of 60° N for October 2017-September 2018 was the second highest (after 2015-2016) in the observational record beginning in 1900. Arctic temperatures for the past five years (2014-2018) all exceed previous records.•Arctic air temperature continues to increase at double the rate of the global mean air temperature increase.•Autumn, winter and spring months all contributed positive anomalies to the annual average temperature. These conditions were supported by advection of heat and moisture from the subarctic by north-south wavy jet stream patterns.•During summer, neutral temperature anomalies occurred across the central Arctic Ocean with a low pressure pattern. Like summer 2016 and 2017, 2018 weather conditions did not support rapid summer sea ice and ice sheet loss.